Kernel weight and source/sink ratio determination of temperate maize hybrids with different end uses under contrasting environments - Chazarreta, Yésica Daniela (2024)
Maize (Zea mays L.) production in Argentina changed markedly during the last decade due to the widespread adoption of late sowings, expanding its productive area, and diversifying crop end-uses. This study evaluated environment (two years × two sowing dates) and management practices (two nitrogen levels) effects on kernel weight, its physiological determinants, source/sink ratios, and water-soluble carbohydrates in stem (WSCS) of eight temperate maize hybrids bred for different uses (3 graniferous, 2 dual-purpose, 2 silage). Crop growth simulations allowed the estimation of percent variation in WSCS remobilization (null, partial, or total) for different production systems (18 scenarios) and climate conditions (41 growing seasons). Nitrogen fertilization increased kernel weight in early sowings, with minimal effects in late sowings. WSCS remobilization during kernel filling was higher in late than in early sowings, with no differences among hybrid types. Regarding hybrid types, dual-purpose and silage hybrids showed the highest and the lowest kernel weight respectively, and graniferous hybrids had the highest source/sink ratio during the effective kernel-filling period. Simulations underscored the importance of sowing date and nitrogen supply on WSCS for irrigated and dryland maize farming systems in a temperate environment, with important implications for grain and silage production at the farm level.